Towards a Sexual Politic of Differences - Durán Sandova, Manuel Alejandro (Universidad de Chile. Programa Domeyko, 2012)
This essay rises from the discussion on "Policies of equality", regarding citizen movements in Chile. It seeks to visualize the mechanisms of recognition of the gay movements and the assimilation policies they have adopted, in their negotiation with the liberal, patriarchal and heterosexist system. Such negotiations exclude many diverging sexual practices and identities that take place outside of formal emotional relations. We have to ask ourselves if we are willing to assume the same programs of sexual and affective normalization of hetero-normativity, and risk generating new exclusions? In this context, queer politics might mean an alternative proposal, considering the assimilation and marriage policies of the gay movements, establishing a "new Ethic of Affectivities".